Return to Galileo? The Inquisition of the International Narcotic Control Board - Small Dan; Drucker Ernest (BMC, 2008)
Abstract Nearly 400 years after Galileo Galilei of Florence was arraigned and convicted of suspected heresy by the ten member Congregation of the Holy Office (Inquisition), the International Narcotic Control Board (INCB) is similarly inserting itself into matters pertaining to innovations in healthcare and the public health response to addiction throughout the world. Like that earlier Inquisition of 1633 that convicted Galileo of heresy for holding that the sun is the centre of the universe with the earth revolving around it (in contradiction to church doctrine of the time) the INCB and its thirteen-member panel, now rails against any evidence out of sync with the established doctrine of the war on drugs - particularly those innovations in public health called harm reduction. The latest healthcare and harm reduction practices to attract the ire of the INCB Inquisition are elements of Canada's most effective and innovative measures to minimize the harms of drugs in Vancouver - supervised injection facilities and, recently, the potential establishment of supervised inhalation rooms - along with the long established practice of providing safer mouthpieces for pulmonary inhalation in British Columbia. This is particularly significant as it comes in the midst of a crucial battle between municipal and provincial authorities in BC with the federal government in Ottawa, which seems determined to undermine all the most effective HR programs that are the result of years of steady local and governmental support in Vancouver and now threatens to derail all these programs and spread doubt about their usefulness despite the overwhelmingly positive findings of serous research.